The Effect of Credit Rating Changes on Common Stock Return-Evidence from the UK Market - Wang, Xueying (2019)
This paper works to study the abnormal price impact from the long-term issuers’ credit rating change announcement on the issuers’ stock in UK market in 2010-2018. Using a standard event study method, we employ several tests statistics on the excess return around the rating change date. The significance test results suggest that the price impact on stocks of the upgrading event is insignificant and the price impact on the respective common stock of the downgrading event is significant, and we conclude that the downgrade rating change contains new information while the upgrade rating change contains no additional information or the effect is offset by the wealth redistribution effect. The multi-variable regression is constructed for window (0,1), (0,3) and (0,5) to determine the possible factors leading to the window cumulative excess return.